Success of Pregnancy in a Patient on High-Volume Hemodiafiltration with Citrate-Acidified Dialysate - Gaelle Pelle; Arwa Jalal Eddine; Philippe Rieu; Julie Attias; Stephanie Fay; Alexandre Hertig (Case Reports in Nephrology and Dialysis, 2023)
Although pregnancy in dialysis patients is rare, recent reports in the literature have shown improvement in pregnancy outcome in this population. Increasing doses of dialysis have led to improvement in fetal prognosis, but recommendations are still lacking, and there are few documented reports of pregnant woman on high-volume online hemodiafiltration. Here, we report the first successful pregnancy in a 28-year-old patient on daily high-volume online post-dilution hemodiafiltration with a citrate dialysate. At 37 weeks and 1 day, she delivered a healthy 2.3 kg baby that did not require neonatal intensive care. This case report suggests that hemodiafiltration with a dialysate acidified with citrate is safe in pregnancy. Further reports and a registry are necessary to confirm that high-volume online hemodiafiltration with a citrate dialysate should be the preferred dialysis modality in pregnant women.